Single-chain recombinant clotting factor VIII (lonoctocog alfa): clinical experience in Russia - M. V. Kosinova (Лечащий Врач, 2022)
Despite significant progress in haemophilia treatment, achieved in Russia recently, number of unmet medical needs still exist in routine clinical practice. Particularly, the annual bleeding rates are still high, leading to frequent development of synovitis and haemophilic arthropathy, resulting in chronic pain and impaired joint motility. Thus, the quality of life of patients with haemophilia is not optimal. One of potential approaches to improve the situation could be more wide use in routine clinical practice recombinant clotting factors with extended half-life. According to modern clinical guidelines on haemophilia treatment, such products could potentially significantly decrease number of infusions for prophylactic therapy without decrease in efficacy of haemostasis control or keeping the same infusion frequency could increase the clotting factors activity, improving the patient’s protection from bleeds. Thus, use of recombinant clotting factors with extended half-life can increase the patient’s compliance to treatment and the results of therapy. One of such molecules is single-chain recombinant clotting factor VIII (lonoctocog alfa). The modification of this molecule leads to improvement of its stability and affinity to von Willebrand factor, allowing to increase the intervals between infusion up to 2-3 times per week for all age groups. This article describes the clinical trial program of lonoctocog alfa and summarize the results of its use among haemophilia patients in Russia. Large international clinical program AFFINITY has demonstrated high efficacy and favorable safety profile of lonoctocog alfa and the analysis of Russian patient’s treatment results demonstrated, that they are in line with such results worldwide.